ANALISIS YURIDIS RECOVERY ASSET MELALUI TINDAK PIDANA PENCUCIAN UANG DARI HASIL TINDAK PIDANA KORUPSI - Iffana Hayu; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Eradication of criminal acts of corruption is the main agenda that must be held. Assetrecovery in corruption is the process of handling assets from the proceeds of corruption at everystage of law enforcement, so that the value of these assets can be maintained and returned to thestate. In Law No. 8 of 2010 Concerning the Prevention and Eradication of Money Laundering,there is a policy related to the law on eradicating corruption and other similar laws, namely withthe sole aim of narrowing down the occurrence of corruption. This means that the presence ofthe Law on Money Laundering is an attempt to assist the operation of the Law on CorruptionEradication.The purpose of this study is to offer an effective and efficient strategy in returning state assetsfrom corruption through money laundering and to find out the construction of the judge'sthinking in examining and deciding money laundering cases on corruption as the predicatecrime.An effective and efficient strategy in efforts to recover assets from the proceeds of corruptionthrough money laundering is to combine charges of corruption with money laundering.Accumulating criminal acts, indictments are not combined with alternative or subsidiary formsand returning assets from the proceeds of criminal acts of corruption can be carried out throughcriminal or civil instruments. The judge's thinking construction regarding evidence that has beenused in other crimes that have permanent legal force (BHT) cannot be used as evidence in othercrimes. The formulation of the crime of money laundering as a supplementary crime ofcorruption (predicate crime) needs to be given the same serious attention as proving thatcorruption is a predicate crime. The unpaid payment for the purchase of an asset becomes aconsideration for the Panel of Judges that the asset is confiscated for the state.Research in making effective and efficient indictment formulations to optimally return stateassets needs to be carried out also for the future. Researchers hope that there will be more in-depth research on efforts to return state assets from the proceeds of criminal acts of corruptionthrough money laundering and other efforts as well as research in making effective and efficientindictment formulations. Efforts to return state assets outside the criminal corridor must be amore serious concern to be carried out.Keywords: Asset Recovery, -Criminal Corruption, -Judge Contruction, -Money LaunderingCrimes